Factors associated with access to healthcare services for older adults with limited activities of daily living - Mai, Shumin; Cai, Jingjing; Li, Lu (Frontiers in Public Health, 2022)
Background: Limited studies focused on the situation and related factors of access to healthcare services for older adults with limited activities of daily living (ADL) in China. This study explores factors associated with access to healthcare services of them based on Andersen’s healthcare utilization model (including need, predisposing, and enabling dimensions). Methods: A total of 3,980 participants aged 65 years and older adults with limited ADL from the latest wave (2018) of the Chinese Longitudinal Healthy Longevity Survey (CLHLS) were included. Binary logistic regression was used to explore the influencing factors. Results: Factors in enabling dimension were associated with access to healthcare services for older adults with limited ADL. Those who lived with better economic status (fair vs poor, OR=2.98, P <0.01; rich vs poor, OR=7.23, P =0.01), could afford daily life (yes vs no, OR=2.33, P=0.03), and lived in the eastern or central region of China (eastern vs western, OR=2.91, P <0.01; central vs western, OR=2.40, P=0.02) could access to healthcare services more easily. However, factors in predisposing dimension and need dimension showed no statistical significance. Meanwhile, inconvenience in the movement was the major barrier reported by some participants for not going to the hospital when they got sick. Conclusions: Access to healthcare services for older adults with ADL limitation was mainly related to the factors of economic status, affordability for daily life, and living regions in enabling dimension. Strategies focused on health insurance, health care system, barrier-free facilities, and social support were proposed to increase the access to healthcare services for participants, which could benefit their health.